Identification and genetic characteristics of tusavirus in fecal samples of patients with chronic diseases in Guangzhou, China - He, Huan; Li, Yongzhi; Chen, Jiaqi; Xian, Juxian; Zheng, Liting; Sun, Hengbiao; Fan, Shunchang; Fu, Jiaqi; Li, Qiushuang; Chen, Caiyun; Liang, Minyi; Zhang, Minyi; et al. (Frontiers in Microbiology, 2023)
Purpose The Tunisian stool-associated parvovirus [Tusavirus (TuV)] is a novel member of the genus Protoparvovirus, which may be linked to diarrhea. Herein, we investigated the prevalence of TuV in different populations and analyzed its genetic and bioinformatic characteristics. Methods This study was conducted in a tertiary hospital in Guangzhou (China) from February 2018 to July 2022. Demographic and clinical information and stool samples were collected from individuals who visited the hospital. ProtScale, SwissModel, Datamonkey, and other tools were used to analyze and predict the physicochemical parameters, tertiary structure, selection pressure, and B-cell epitopes of capsid viral protein 2 of TuV (VP2-TuV). Results A total of 3,837 participants were enrolled, among which two stool samples from patients with chronic illnesses were tested positive for TuV DNA. However, no positive sample was detected among patients with diarrhea. Two near-complete genome sequences were amplified. The genetic analysis revealed the presence of diversity among TuVs isolated from distinct host species. Bioinformatics analysis revealed that VP2-TuV exhibited hydrophilic properties and lacked transmembrane domains and signal peptides. The secondary structure of VP2-TuV was composed mainly of random coils and β-strands. Selective-pressure analysis of the VP2 region suggested that TuV primarily underwent negative selection during evolution. Negatively selected codon sites coincided with residues comprising of B-cell epitopes, suggesting minimal changes in the immunogenicity of TuV over time. Conclusion TuV was detected in patients with chronic diseases but not in patients with diarrhea. The putative roles of TuV in the pathogenicity of human diseases and zoonotic viruses must be determined by additional studies.